2016
DOI: 10.4103/1305-7456.195159
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of behavioral modification techniques with visual distraction using intrasulcular local anesthesia in hearing disabled children during pulp therapy

Abstract: Objective:Assessing the effectiveness of behavioral modification techniques in combination with visual distraction with/without video eyewear using computerized delivery system-intrasulcular (CDS-IS) during the application of local anesthetic in hearing-impaired pediatric patients undergoing pulp therapy of primary molars.Materials and Methods:This randomized, crossover clinical study includes 15 children (7 boys and 8 girls), mean age was 6.1 years. Children were randomly distributed into two groups (Group A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 12 publications
4
16
0
4
Order By: Relevance
“…In respect to pain, Asvanund's study reported that audiovisual eyeglasses significantly reduced pain scores is consistent with our review . But in 2016, Fakhruddin's study reported the results of pain is inconsistent between groups . Regarding behavior, Isong's results support our review .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In respect to pain, Asvanund's study reported that audiovisual eyeglasses significantly reduced pain scores is consistent with our review . But in 2016, Fakhruddin's study reported the results of pain is inconsistent between groups . Regarding behavior, Isong's results support our review .…”
Section: Discussionsupporting
confidence: 88%
“…With respect to pulse rate, Asvanund and Sullivan's studies were consistent with our review . Fakhruddin's results are inconsistent between groups; however, Vincent and Isong's trial found no significant difference in pulse rate . In the matter of children satisfaction, some studies showed that subjects preferred using audiovisual distraction during dental treatment which supports our review.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Of the abovementioned psychological management techniques, the tell-show-do, distraction and molding techniques are seen as good alternatives for reducing anxiety and fear in children during dental treatment, as indicated by the studies of Rezende et al 2 and Fakhruddin et.al. 17 . Unlike in the literature, however, these psychological tactics were not successful in permitting adequate dental treatment and the attempt to become the patient's friend was almost always hampered, mainly due to the mother's conduct.…”
Section: Discussionmentioning
confidence: 99%
“…However, the operating field should remain fully visible, although in the case of patients with no hearing issues, watching pictures on a screen is less effective than using VR goggles. This may be due to the fact that children with impaired hearing have no control over their surroundings and experience anxiety whenever they are unable to maintain visual contact [33].…”
Section: Alternative Methodsmentioning
confidence: 99%